Capital income taxation and risk taking under prospect theory - Jaroslava Hlouskova; Panagiotis Tsigaris (Institute for Advanced Studies (IHS), 2012)
This research examines capital income taxation for a loss averse investor under some acceptable in the literature reference levels relative to which are the changes in the level of wealth valued. Depending on the reference level, some results indicate that it could be possible for a capital income tax increase not to stimulate risk taking even if the tax code provides the attractive full loss offset provisions. However, risk taking can be stimulated if the investor interprets part of the tax as a loss instead as a reduced gain. Then investor becomes risk seeking and moves away from the discomfort zone of relative losses. This later response to taxation causes private risk taking to increase which is contrary to what evolves from assuming an expected utility model. Finally, a number of other reference standards are examined as well.
Keywords: G11; H2; 330; risk taking; portfolio choice; prospect theory; loss aversion; reference level; taxation